Effects of downy mildew fungi spore infection on cucumber plants under nitrogen stress - Wang, Yafei; Shi, Qiang; Du, Xiaoxue; Mao, Hanping; Taha, Mohamed Farag (International Journal of Agricultural and Biological Engineering, 2026)
Investigating the interplay between biotic stress from downy mildew and abiotic stress from nitrogen deficiency is crucial for improving crop management measures and enhancing cucumber production. A greenhouse experiment was conducted using two pathogen treatments—non-infected (B1) and infected with Pseudoperonospora cubensis (B0)—across three nitrogen levels: deficiency (N1: 50%), optimal (N2: 100%), and excess (N3: 150%). The resulting six treatment combinations (B1N1, B1N2/Control, B1N3, B0N1, B0N2, and B0N3) revealed that downy mildew infection and nitrogen application rates significantly influenced key physiological and biochemical parameters (p<0.05). These included sucrose, soluble sugar, hydrogen peroxide (H2O2), catalase (CAT), superoxide dismutase (SOD), polyphenol oxidase (PPO), and malondialdehyde (MDA), as well as the fresh and dry weights of the leaves, stems, and roots. Among all groups, the combination of infection and nitrogen deficiency (B0N1) had the most significant impact on biomass accumulation and hormone metabolism. Compared to the B1N2 control, B0N1 led to substantial reductions in sucrose (52.83%), soluble sugar (68.67%), leaf fresh weight (56.67%), leaf dry weight (55.51%), stem fresh weight (52.82%), stem dry weight (57.28%), root fresh weight (32.46%), and root dry weight (54.07%). This study clarifies the interactive physiological responses of cucumbers to combined biotic and abiotic stress. It is of great significance for facilitating the control of downy mildew and the improvement of cucumber yield in sustainable agriculture. Keywords: Cucumis sativusL, biotic stress; abiotic stress, physiological metabolism, substance accumulation DOI: 10.25165/j.ijabe.20261902.10264 Citation: Wang Y F, Shi Q, Du X X, Mao H P, Taha M F. Effects of downy mildew fungi spore infection on cucumber plants under nitrogen stress. Int J Agric & Biol Eng, 2026; 19(2): 58–64.